GAMBARAN PERILAKU KELUARGA PENGGUNA JAMKESMAS TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS PIJORKOLING KECAMATAN PADANGSIDIMPUAN TENGGARA KOTA PADANGSIDIMPUAN TAHUN 2012 - aziz anshori; Linda maas; Eddy Syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Implementation of the Community Health Insurance (Jamkesmas) has the objective to improve access and quality of health services to all the poor and underprivileged in order to achieve an optimal level of public health effectively and efficiently. This study was a descriptive survey using a quantitative approach, to describe the behavior of the participants Jamkesmas in using health services in Kecamatan Padangsidimpuan Tenggara. The number of sample of this study was 95 households from 6361 population. The results of this study indicated that the knowledge of the respondents were generally in the category “not good” amounted to 76.8%, the attitude in the category of "medium" amounted to 96.8% and the action included in the category of "moderate" amounted to 50,5 %. The health workers were expected to provide good services either promotive, curative or rehabilitative to the Jamkesmas participants. The Head of Health Center was suggested to observe and provide health facilities required to carry out health services so that participants Jamkesmas would be more convenient using health care facilities.